Inhibitory effects of selected dietary flavonoids on the formation of total heterocyclic amines and 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) in roast beef patties and in chemical models. Issue 2 (19th January 2016) - Zhu, Qin; Zhang, Shuang; Wang, Mingfu; Chen, Jie; Zheng, Zong-Ping
Abstract : Dietary flavonoids effectively inhibit total HAs and PhIP formation in roast beef patties through scavenging of intermediates in formation pathways. Abstract : In this study, the inhibitory effects of eight kinds of dietary flavonoids on the formation of heterocyclic amines (HAs) were investigated in roast beef patties. The results showed that most of them exhibited significant inhibition on both total HAs and 2-amino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine (PhIP), one of the most abundant HAs. Among the studied flavonoids, phlorizin, epigallocatechin gallate (EGCG), and quercetin were found to be the most effective in both the reductions of total HAs (55–70%) and PhIP (60–80%). The reaction activity between the flavonoid and phenylacetaldehyde, a key intermediate in PhIP formation, showed a good correlation with the inhibition of PhIP formation in an aqueous model system ( R 2 = 0.8904) and a di(ethylene) glycol reaction system ( R 2 = 0.6514). However, no significant correlation was found between the flavonoid antioxidant capacity and PhIP formation ( R 2 = 0.2359). The postulated adducts of flavonoids–phenylacetaldehyde were further confirmed by LC-MS analysis in the chemical models. Since phenylacetaldehyde is the chief intermediate in PhIP formation, these results suggest that the inhibitory effects of flavonoids on PhIP formation are mainly dependent on their abilities to trap phenylacetaldehyde as opposed to their antioxidant capacities.